Building an Infrastructure Level Context Model in Ambient Assisted Living - Wojciechowski, Manfred (Electronic Communications of the EASST, 2010)
Ambient Assisted Living (AAL) services provide intelligent and context aware assistance for elderly people in their home environment. This domain puts special requirements on context modeling that are not in the scope of current context modeling approaches. Such an approach has to support all phases of an AAL service, from its specification and development until its operation within the user’s smart home environment. In these phases different types of context models can be identified. We have developed a comprehensive context modeling approach for the development of AAL services. Part of it is the separation of context modeling into infrastructure, service adaptation and end user modeling specific aspects. In this paper we focus on the infrastructure, which includes the context sensors available in the smart home environment. Therein we present our context modeling approach starting from a conceptual context model. We also introduce a context management system based on a metamodel that supports its seamless transition into an operative context model without further implementation.